Correlation between Basic Immunization Status and IHC Visits to Stunting Incidents on Toddlers - Jessica Azzahra Diva; Citra Windani Mambang Sari; Laili Rahayuwati; Kosim Kosim (Journal of Nursing Care, 2023)
Stunting could be found in a circumstance where children's height is unusual compared to their age. There are multifactor that cause stunting which some of them are repeated infections and the utilization of health services. Recurrent infections can be prevented if the child's basic immunization is complete. A complete history of immunization status can lower the incidence of recurrent infections. In addition, ANC examinations and measurements of weight and height as the form of the utilization of health services are perceivable by the frequency of visits of mothers and toddlers to integrated healthcare. The more frequently mothers and toddlers go to integrated healthcare, the faster stunting symptoms will be detected thus the toddler is less likely to experience stunting. This study aims to examine associations between toddlers' basic immunization status and visits to integrated healthcare regarding the stunting incidence among toddlers at the stunting locus in Sukamulya Village, Bandung Regency. The study used a quantitative correlation design with a secondary data approach. Respondents are acquired from secondary data, which is the society in Sukamulya Village, Bandung Regency. Samples were selected through purposive sampling technique with specific criteria which is mother with children under five, resulting 96 people in total. The variables in the study consisted of basic immunization status, visits to integrated healthcare, and stunting. Data processing uses univariate and bivariate analysis. The instrument consists of a toddler’s immunization history, ANC examination, also toddler’s weight and height measurement. Statistical test using Chi square with 5% significance level. This study results that there are no associations between basic immunization status (p value = 0.284) with stunting incident and visits to integrated healthcare is associated with (p value = 0.001) the incidence of stunting. These findings are caused by the variety of immunity levels of toddlers and there are multifactor that cause infectious diseases.